Oral health and diet in populations of Central Argentina during the late holocene: Bioarchaeological and isotopic evidence - Fabra, Mariana (2019)
We studied the temporal and spatial variation of diet and oral health of human populations that inhabited the central region of Argentina during the Late Holocene (4000-300 BP) by evaluating isotopic data (δ13Ccol, δ15N), physiological stress indicators (tooth wear), and infectious dental diseases (caries). The sample of 49 individuals was recovered from archaeological sites located in the province of Córdoba, dated by AMS on collagen to a range of 4058 ± 89 years BP to 370 ± 15 14C years BP. After calculating the prevalence of caries and the average dental wear, we compared these values based on regional origin (central highlands and eastern lowlands), temporal assignation (early Late Holocene, late Late Holocene), and sex (female and male). We found clear regional and temporal differentiation, which we interpret as resulting from differential use of plant resources among the regions and a slight deterioration in oral health in the Late Holocene. Stable isotope analysis indicates food consumption of C3 and C4 resources, although the observed temporal variations in the isotopic values may indicate an introduction of C4 resources in the later Late Holocene, mainly in the mountainous region.